2016
DOI: 10.1039/c6gc00415f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a series of amino acid derived ionic liquids and tertiary amines: green chemistry metrics including microbial toxicity and preliminary biodegradation data analysis

Abstract: A series of L-phenylalanine ionic liquids (ILs), L-tyrosine ILs, tertiary amino analogues and proposed transformation products (PTPs) have been synthesised. Antimicrobial toxicity data, as part of the green chemistry metrics evaluation and to supplement preliminary biodegradation studies, was determined for ILs, tertiary amino analogues and PTPs. Good to very good overall yields (76 to 87%) for the synthesis of 6 ILs from L-phenylalanine were achieved. A C 2 -symmetric IL was prepared from TMS-imidazole in a o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 69 publications
5
55
1
Order By: Relevance
“…To prove the presupposed idea, various studies with new amino‐acid‐based ILs have been performed, including those with bacteria and fungi. For example, Jordan et al . have evaluated the antimicrobial activity of a series of l ‐phenylalanine ILs, l ‐tyrosine ILs, and tertiary amino analogues with 8 bacteria and 12 fungi strains.…”
Section: Toxicological Impact Of Ionic Liquidsmentioning
confidence: 99%
See 2 more Smart Citations
“…To prove the presupposed idea, various studies with new amino‐acid‐based ILs have been performed, including those with bacteria and fungi. For example, Jordan et al . have evaluated the antimicrobial activity of a series of l ‐phenylalanine ILs, l ‐tyrosine ILs, and tertiary amino analogues with 8 bacteria and 12 fungi strains.…”
Section: Toxicological Impact Of Ionic Liquidsmentioning
confidence: 99%
“…Other approaches have been applied to upgrade the synthesis of ILs, for example, the use of benign solvents or solventfree processes, the use of recyclable solvents, the design and creationo fs afer chemical products that are harmless and biodegradable, and ar eduction in waste production.F or example, variousauthors have synthesized new ILs from renewable sources, such as nicotinic acid, [38] choline, [39] sugars, [40] and amino acids. [41] Furthermore, new generationso fs alts, such as deep eutectics olvents (DESs) show good performance in chemical reactions. The synthesis of DESs simply involves mixingt wo cheap componentsw ith low environmental impact together www.chemsuschem.org to form ae utectic mixture without the need for any additional solvents.…”
Section: Concerns About the Greenness Of Ionic Liquid Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…However, the level of toxicity can be reduced by introducing an aryl group instead of an alkyl or allyl group in the cation . Furthermore, cations like morpholinium and cholinium have been found to be the least toxic, and can be used to design inherently safe ILs, especially when combined with short polar side chains and nontoxic anions . The oxygenated group in the cation also decreases toxicity as it contributes to hydrophilicity.…”
Section: Toxicity Of Ionic Liquids Toward Microorganismsmentioning
confidence: 99%
“…[84] Furthermore, cations like morpholinium and cholinium have been found to be the least toxic, and can be used to design inherently safe ILs, especially when combined with short polar side chains and nontoxic anions. [26,[85][86][87][88] The oxygenated group in the cation also decreases toxicity as it contributes to hydrophilicity. Mustahil et al [87] reported new antimicrobial surface active ILs with cations named pyrrolidinium, imidazolium, pyridinium, piperidinium, morpholinium, and cholinium, and lauroyl sarcosinate as an anion.…”
Section: Effect Of Cationsmentioning
confidence: 99%